Transcriptome analysis of unsaturated fatty acids biosynthesis shows essential genes in sprouting of Acer truncatum Bunge seeds. (June 2021) - Chen, Dong-Ju; Luo, Xue-Gang; Yan, Li-Hua; Si, Chuan-Ling; Wang, Nan; He, Hong-Peng; Zhang, Tong-Cun
Abstract: The seeds of Acer truncatum Bunge ( ATB ) are rich in unsaturated fatty acids (UFA), especially nervonic acid, an important nutrient for the growth and maintenance of the brain. Therefore, the oil of ATB seeds has been approved as a New Resource Food in China. In the present study, changes of transcriptomic profiling and contents of UFA during the sprouting of ATB seeds were analyzed. The results of RNA-seq-based transcriptome analysis showed that the transcription of genes in various metabolic pathways, including the biosynthesis pathway of UFA, were significantly altered during seed sprouting. The gas chromatography-mass spectrometry assay consistently showed that the content of palmitoleic acid, palmitic acid, stearic acid, gondoic acid, arachidic acid, behenic acid, nervonic acid and lignoceric acid increased 77.9, 20.9, 39.6, 26.3, 95.6, 80.0, 41.7 and 141%, respectively, while the content of oleic acid decreased 49.2%, after sprouting. The whole coding sequence regions of genes involved in the UFA biosynthesis were cloned and sequenced, and the alignment analysis predicted that omega-6 fatty acid desaturase and short-chain type dehydrogenase/reductase might have important roles in the biosynthesis of UFA during the sprouting. The results suggested that nervonic acid could be enriched in ATB seeds via sprouting-stimulation, which had not been previously observed.